Testing for constant correlation by means of trigonometric functions - Matthias J. Fischer (Friedrich-Alexander-Universität Erlangen-Nürnburg, Lehrstuhl für Statistik und Ökonometrie, 2006)
A new test for constant correlation is proposed. The TC-test is derived as Lagrange multiplier (LM) test. Whereas most of the traditional tests (e.g. Jennrich, 1970, Tang, 1995 and Goetzmann, Li & Rouwenhorst, 2005) specify the unknown correlations as piecewise constant, our model-setup for the correlation coefficient is based on trigonometric functions. The simulation results demonstrate that the TC-test guarantees correct empirical size, is powerful against many alternatives and able to detect structural breaks in correlations. Finally, application of the TC-test to foreign exchange rate data over the period of 15 years is given.
Keywords: 330